Influência do deságue do sistema de lagoas de estabilização na quantidade de nutrientes no Igarapé Grande, Boa Vista, Roraima - Esbell, Diane Macedo (2006)
The igarapé (small streams) Grande, in Boa Vista, Roraima, is the receiving body of the wasterwater generated starting from the waste stabilization ponds, system of treatment of the sanitary sewers of part of the city. By the hypothesis that the spilling of those wasterwater in referred him body of water contributes so that the same presents physiochemical characteristics that you/they implicate in her degradation, lasting long in a similar way for good part of the course of water, mainly in the mount of nutrients, a manegament hydric resouses the behavior of physiochemical parameters was accomplished in that hydric body by the whole year 2005. It was observed the sazonality of the area, drought and flood. Concentrations of ammonia were analyzed, nitrite, nitrate, sulfate and phosphate, besides pH, BOD, DO, temperature and electric conductivity in samples of water of the igarapé(small streams) Grande, collected to amount of the spilling of the wasterwater, in the place of spilling of the wasterwater and to the downstream. The collect techniques, preservation of the samples and analyses, they obeyed Standart Method’s for Examination of Water and Wasterwater. The chemometrics treatment of the data was accomplished through average, standard deviation, variance, variation coefficient, estimate of mistake of analytical curve, tests F (5%) and t (95%) and exploratory analysis of data (PCA and HCA). The results indicate the contribution of the wasterwater in the increase of the concentration of nutrients for the whole studied period, being observed a distinction among the analyzed points and among the periods I dry and full. The middlestream always came more similar in relation to the downstream while to amount it maintained differentiated her. The nitrate was the nutrient that more contributed to the distinction observed among the periods dry and full, as well as increase of BOD, pH, conductivity and DO and temperature, respectively. The distinction among the analyzed points happened mainly as a consequence of the high concentrations of ammonia. Therefore, there is need of a specific powder-treatment in the waste stabilization pond, in order to reduce the amount of nutrients in the igarapé Grande, because the impacts that the wasterwater is causing to the receiving body, consequently, besides to make unfeasible the use of the water in her course and to cause other damages, it contributes to worsen the eutrofization.